Macroscopic approaches to the identification of expedient bivalve tools: A case study investigating Polymesoda (=Geloina) coaxans (Bivalvia: Corbiculidae) shell valves from Princess Charlotte Bay, Queensland, Australia. (5th January 2017) - Harris, Matthew; Faulkner, Patrick; Asmussen, Brit
Abstract: The identification of expedient bivalve tools recovered from archaeological deposits is currently hindered by a lack of analytical frameworks. In order to identify those shell valves which have been used as expedient tools, analysts must be able to identify and distinguish between pre-mortem and post-depositional modifications, and use-wear from tool use. Central to this difficulty is a lack of experimental analogues for comparison with archaeological material. Here, we present an analytical framework for the identification of expedient bivalve tools made from Polymesoda (= Geloina ) coaxans valves recovered from Australian archaeological sites. This analytical framework consists of a series of actualistic experiments designed to determine those variables useful for distinguishing between modifications produced via pre-mortem and post-depositional processes that can damage molluscan shell, and damage produced via use as an expedient tool. Trampling, flaking and scraping experiments and use-wear analysis are used as a reference for comparison with an assemblage of P . coaxans valves recovered from archaeological sites in Princess Charlotte Bay, north Queensland, Australia. We demonstrate that an analytical framework consisting of an analysis of shell area loss, shell fracture paths, and use-wear can be successfully applied to archaeological samples to confidently distinguish between those valves which have been used as expedient tools, and those which have not. This research has wider implications for the identification of this often overlooked class of shell tools from archaeological sites in Australia and other regions, allowing a more comprehensive understanding of the place of shell tools in coastal economies of the past.